WRITING BEHAVIORAL OBJECTIVES: A NEW APPROACH (Author: H.H. McAshan) - McKay, Gerald (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1971)
H.H. McAshan. WRITING BEHAVIORAL OBJECTIVES: A NEW APPROACH. Reviews New York: Haper and Row. 1970. 116 pp. 2.50.